A Comparison of Hemostatic Changes in Splenectomized and Nonsplenectomized β-Thalassemia Intermedia Patients. Issue 8 (November 2016) - Hashemieh, Mozhgan; Azarkeivan, Azita; Sheibani, Kourosh
Abstract : The present study was conducted to compare the coagulation factors between splenectomized and nonsplenectomized thalassemia intermedia (TI) patients as well as a healthy control group. A total of 60 splenectomized and 60 nonsplenectomized TI patients and 60 healthy controls participated in this case-control study. The level of homocysteine, protein C and S, antithrombin III, factors V and VIII, fibrinogen, and D-dimer were measured in all groups. Our results indicated a significant reduction of protein C and S and fibrinogen in TI patients compared with healthy controls ( P <0.001), as well as factor V activity ( P =0.009). Also a significant elevation of D-dimer ( P =0.006) and factor VIII activity ( P =0.001) was observed. There was no significant difference considering homocysteine and antithrombin III level among patients and healthy controls. Also our results demonstrated that there was no significant difference considering the homeostatic parameters (except D-dimer activity) between splenectomized and nonsplenectomized TI patients after adjustment for age. In conclusion, reduction of protein C and S, fibrinogen, and factor V activity and elevation of D-dimer levels and factor VIII activity was observed in TI patients compared with healthy controls. It seems that splenectomy has little significant effect on concentration of hemostatic factors except for D-dimer activity.